ENU Mutagenesis Screen to Establish Motor Phenotypes in Wild-Type Mice and Modifiers of a Pre-Existing Motor Phenotype in Tau Mutant Mice. (15th December 2011) - Liu, Xin; Dobbie, Michael; Tunningley, Rob; Whittle, Belinda; Zhang, Yafei; Ittner, Lars M.; Götz, Jürgen
Abstract : Modifier screening is a powerful genetic tool. While not widely used in the vertebrate system, we applied these tools to transgenic mouse strains that recapitulate key aspects of Alzheimer's disease (AD), such as tau-expressing mice. These are characterized by a robust pathology including both motor and memory impairment. The phenotype can be modulated by ENU mutagenesis, which results in novel mutant mouse strains and allows identifying the underlying gene/mutation. Here we discuss this strategy in detail. We firstly obtained pedigrees that modify the tau-related motor phenotype, with mapping ongoing. We further obtained transgene-independent motor pedigrees: (i) hyperactive, circling ENU 37 mice with a causal mutation in the Tbx1 gene—the complete knock-out of Tbx1 models DiGeorge Syndrome; (ii) ENU12/301 mice that show sudden jerky movements and tremor constantly; they have a causal mutation in the Kcnq1 gene, modelling aspects of the Romano-Ward and Jervell and Lange-Nielsen syndromes; and (iii) ENU16/069 mice with tremor and hypermetric gait that have a causal mutation in the Mpz ( Myelin Protein Zero ) gene, modelling Charcot-Marie-Tooth disease type 1 (CMT1B). Together, we provide evidence for a real potential of an ENU mutagenesis to dissect motor functions in wild-type and tau mutant mice.